URGENSI CAGAR BUDAYA BAGI MASYARAKAT - Aurelia Tanesi; Blajan Konradus (Jurnal Pluralis, 2024)
Cultural heritage is a cultural heritage that has an important meaning as a national identity, because it has a number of values ​​that can be said as the foundation of the Indonesian life. Dealing with the development of globalization, many of Indonesian people are facing various business offers and economic needs as well as improvements and even changes in lifestyle, so that many of them they sell various personal assets, even without compromising with the family, someone can sell or mortgage a number of family assets in the form of land and other things to investors or large capital owners, including knowingly and deliberately occupying and buying and selling land on which there are suspected objects. as a cultural heritage. The goods or objects being traded include assets belonging to certain families, indigenius communities, as well as the government in the form of cultural heritage objects, cultural heritage structures, cultural heritage buildings, cultural heritage sites and certain cultural heritage areas. For this reason, socialization is needed for the community to maintain and preserve cultural heritage throughout the country.